Catalysing actionable knowledge for youth entrepreneurship: Participants' experience - Nsanganira, Tony R. (Technical Centre for Agricultural and Rural Cooperation, 2018)
Tony Nsanganira, Youth Employment in Agribusiness Specialist at FAO, shares some insights on the process of workshop and its outcomes.